Pemetaan SIG Batas RT/RW dengan Tag Nama Kepala Keluarga Pada Desa Curahmalang Sumobito Jombang - Emi Lilawati; Siti Sufaidah; Chusnul Chotimah; Aris Nur Mahendra; Muhammad Daniriyan Permana; Mohammad Frastio; Abdul Misbahuddin (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
This community service aimed to improve the effectiveness of public information services in Curahmalang Village through the development and implementation of a Geographic Information System (GIS)-based application. The program focused on mapping village data, creating a digital database of households, and producing printed maps to support administrative transparency and public information. Activities included socialization, training on system use for village officials, and publication on the official Unwaha website to reach a broader audience. As a result, the village gained an integrated digital map and a more efficient information service mechanism, which also encouraged public participation in data updating and supported the vision of a smart village.